Oropharyngeal Manifestations in Patients with HIV from Northeastern Romania - Amelia Elena Surdu; Isabela Ioana Loghin; Victor Daniel Dorobăţ; Vlad Hârtie; Șerban Alin Rusu; Ion Cecan; Amelia Andreea Mihăescu; Otilia Eva; Carmen Mihaela Dorobăț (Medicina)
Backgrounds and objective: Disorders in the stomatognathic system and otorhinolaryngologic manifestations are frequently observed in individuals living with HIV. Ear, neck, and throat (ENT) signs and symptoms often serve as critical markers of treatment failure, particularly in the advanced stages of HIV infection. This article aims to evaluate and consolidate recent developments in the treatment and management of otorhinolaryngological manifestations in HIV-positive patients. Materials and methods: We carried out a retrospective clinical investigation of patients admitted with HIV/AIDS in the northeastern region of Romania, hospitalized in the “St. Parascheva” Clinical Hospital of Infectious Diseases in Iasi. We followed the viro-immunological status correlated with patients’ otolaryngology and dental symptomatology, aiming to emphasize the comorbidities of HIV/AIDS cases. The study period spanned from 1 January 2020 to 30 November 2024. Results: There were a total of 552 recorded cases of oropharyngeal manifestations in patients with HIV. They were more frequent in men (358 cases, 64.85%) than women (194 cases, 35.15%). The majority of cases were young adults, aged 30 to 39 years, comprising 255 patients (46.19%), and most cases (36.85%) had CD4+ T-lymphocyte values between 200 and 499 cells/μL. The most frequent diagnosis was oral candidiasis, recorded in 335 male and 174 female cases (509, 92.21% total). Other notable conditions included gingivitis/periodontitis, sinusitis/rhinosinusitis, mastoiditis, and dental abscesses, albeit at lower frequencies. Notably, antifungal therapy with fluconazole was the most frequently employed treatment, followed by aminopenicillins and fluoroquinolones. With respect to the antiretroviral treatment, 83.69% of cases were prescribed a single-pill regimen. Conclusions: The key to the management of HIV-positive patients is a multidisciplinary approach, including an ENT specialist and access to antiretroviral therapy.